Effective Use of Water in Crop Plants in Dryland Agriculture: Implications of Reactive Oxygen Species and Antioxidative System - Rane, Jagadish; Singh, Ajay Kumar; Tiwari, Manish; Prasad, P. V. Vara; Jagadish, S. V. Krishna (Frontiers in Plant Science, 2022)
Under dryland conditions, annual and perennial food crops are exposed to dry spells, severely affecting crop productivity by limiting available soil moisture at critical and sensitive growth stages. Climate variability continues to be the primary cause of uncertainty, often making timing rather than quantity of precipitation the foremost concern. Therefore, mitigation and management of stress experienced by plants due to limited soil moisture are crucial for sustaining crop productivity under current and future harsher environments. Hence, the information generated so far through multiple investigations on mechanisms inducing drought tolerance in plants needs to be translated into tools and techniques for stress management. Scope to accomplish this exists in the inherent capacity of plants to manage stress at the cellular level through various mechanisms. One of the most extensively studied but not conclusive physiological phenomena is the balance between reactive oxygen species (ROS) production and scavenging them through an antioxidative system (AOS), which determines a wide range of damage to the cell, organ, and the plant. In this context, this review aims to examine the possible roles of the ROS-AOS balance in enhancing the effective use of water (EUW) by crops under water-limited dryland conditions. We refer to EUW as biomass produced by plants with available water under soil moisture stress rather than per unit of water (WUE). We hypothesize that EUW can be enhanced by an appropriate balance between water-saving and growth promotion at the whole-plant level during stress and post-stress recovery periods. The ROS-AOS interactions play a crucial role in water-saving mechanisms and biomass accumulation, resulting from growth processes that include cell division, cell expansion, photosynthesis, and translocation of assimilates. Hence, appropriate strategies for manipulating these processes through genetic improvement and/or application of exogenous compounds can provide practical solutions for improving EUW through the optimized ROS-AOS balance under water-limited dryland conditions. This review deals with the role of ROS-AOS in two major EUW determining processes, namely water use and plant growth. It describes implications of the ROS level or content, ROS-producing, and ROS-scavenging enzymes based on plant water status, which ultimately affects photosynthetic efficiency and growth of plants.